The Antarctic Crust and Upper Mantle: A Flexible 3D Model and Software Framework for Interdisciplinary Research - Stål, Tobias; Reading, Anya M.; Halpin, Jacqueline A.; Phipps, Steven J.; Whittaker, Joanne M. (Frontiers in Earth Science, 2020)
Interdisciplinary research concerning solid Earth-cryosphere interaction, and feedbacks, requires a working model of the Antarctic crust and upper mantle. Active areas of interest include the effect of heterogeneous Earth structure on glacial isostatic adjustment, the distribution of geothermal heat, and the history of erosion and deposition. In response to this research need, we construct an adaptable and updatable 3D grid model in a software framework to contain and process solid Earth data. The computational framework, based on an open source software package 'agrid', allows different data sources to be combined and jointly analysed. The grid model is populated with crustal properties from geological observations and geochronology results, where such data exist, and published segmentation from geophysical data in the interior where direct observations are absent. The grid also contains 3D geophysical data such as wave speed and derived temperature from seismic tomographic models, and 2D datasets such as gravity anomalies, surface elevation, subglacial temperature and ice sheet boundaries. We demonstrate usage of the framework by computing new estimates of subglacial steady-state heat flow in a continental scale model for East Antarctica, and a regional scale model for the Wilkes Basin in Victoria Land. We hope that the 3D model and framework will be used widely across the solid Earth and cryosphere research communities.